Strategi Afrika Selatan Melalui Piala Dunia Sepak Bola 2010 Untuk Perbaikan Citra Negara Pasca Apartheid - Mongkau, Albert Meisiano; Fasisaka, Idin; Prameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This research aims to explain whether the holding of the 2010 Soccer World Cup in South Africa can improve the image of their country. This research uses descriptive qualitative methods. South Africa has a poor country image after the apartheid government. To be able to overcome these problems South Africa tried to use Sports Diplomacy as a way out. Organizing a grand sports event is a form of South African Sports Diplomacy. The Football World Cup is a major sporting event that South Africa wants to develop in order to improve the image of their country. Researchers use the Sports Diplomacy framework through major sporting events to explain the benefits of grand sporting events Keywords: Sport Diplomacy,South Africa, Country Image, Football World Cup 2010